Solving the Equation (x+4)(x+6) = 0
This equation is a quadratic equation in factored form. Let's break down how to solve it:
Understanding the Zero Product Property
The Zero Product Property states that if the product of two or more factors is zero, then at least one of the factors must be zero.
In our equation, (x+4) and (x+6) are the factors. Therefore, for the product to equal zero, either:
 (x+4) = 0 or
 (x+6) = 0
Solving for x

Solve for x in the first equation:
 x + 4 = 0
 x = 4

Solve for x in the second equation:
 x + 6 = 0
 x = 6
Solutions
Therefore, the solutions to the equation (x+4)(x+6) = 0 are:
 x = 4
 x = 6
These are the values of x that make the equation true.